2020
DOI: 10.1021/acsomega.0c02310
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the Novel AT1 Receptor Tracer [18F]Fluoropyridine–Candesartan via Click Chemistry

Abstract: A novel 7-((4-(3-((2-[ 18 F]fluoropyridin-3-yl)oxy)propyl)-1 H -1,2,3-triazol-1-yl)methyl)-1 H -benzo[ d ]imidazole derivative of the angiotensin II type-1 receptor (AT 1 R) blocker candesartan, [ 18 F]fluoropyridine–candesartan, was synthesized via the copper-catalyzed azide–alkyne cycloaddition click reaction between 2-[ 18 F]fluoro-3-(pent-4-yn-1-yl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…The addition of Cu(I)‐stabilizing ligands was demonstrated to accelerate the click reaction kinetics under mild conditions 20,26–29 . Indeed, we found that TBTA, BPDS, or THPTA enhanced the conversion of [ 18 F]FPyKYNE to the desired product (Table 1, entries 4–6), resulting in RCYs ranging from 7% to 17%.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…The addition of Cu(I)‐stabilizing ligands was demonstrated to accelerate the click reaction kinetics under mild conditions 20,26–29 . Indeed, we found that TBTA, BPDS, or THPTA enhanced the conversion of [ 18 F]FPyKYNE to the desired product (Table 1, entries 4–6), resulting in RCYs ranging from 7% to 17%.…”
Section: Resultsmentioning
confidence: 89%
“…In order to minimize the volatilization of the prosthetic group, we reduced the reaction temperature (150°C) and time (5 min). Furthermore, the purification was improved by using semipreparative silica‐gel HPLC 20 . It is important to note that we were not able to find a proper solvent to completely separate [ 18 F]FPyKYNE from NO 2 PyKYNE by C18 HPLC (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Incorporation of 18 F‐labeled prosthetic groups onto biological active compound has been accomplished via acylation, amidation, imidation, alkylation, and photochemical conjugation 11 . Recently, our group developed the novel tracer [ 18 F]fluoropyridine‐Candesartan labeled with the [ 18 F]FPyKYNE prosthetic via the copper‐catalyzed azide‐alkyne cycloaddition at the imidazole 7‐position in 10% yield, high molar activity, and radiochemical purity (≥97%) 12 . Biological studies revealed specific binding of [ 18 F]fluoropyridine‐Candesartan in AT 1 R‐rich tissues such as the kidney cortex.…”
Section: Introductionmentioning
confidence: 99%